2017
DOI: 10.1136/bmjopen-2016-012985
|View full text |Cite
|
Sign up to set email alerts
|

Investigating skin-to-skin care patterns with extremely preterm infants in the NICU and their effect on early cognitive and communication performance: a retrospective cohort study

Abstract: ObjectivesThe primary objective of the study was to investigate how patterns of skin-to-skin care might impact infant early cognitive and communication performance.DesignThis was a retrospective cohort study.SettingThis study took place in a level-IV all-referral neonatal intensive care unit in the Midwest USA specialising in the care of extremely preterm infants.ParticipantsData were collected from the electronic medical records of all extremely preterm infants (gestational age <27 weeks) admitted to the unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Infant post-discharge outcomes were particularly positive among infants from the SFR NICU environment whose mothers also showed high levels of maternal involvement [32]. While a retrospective cohort study of parental skin-to-skin holding of extremely preterm infants, defined by the study's authors as GA < 27 weeks, in the NICU showed a positive but nonsignificant relationship between parents who skin-to-skin held and infant communication development [33], the Family Nurture Intervention trial demonstrated improved cognitive and language outcomes at the 18 month follow-up assessment between intervention and control groups [34]. A longitudinal cohort study followed 81 parent-infant triads over 4–5 years after recording parental visitation, blanket holding, and skin-to-skin holding patterns while preterm infants were hospitalized in the NICU.…”
Section: Resultsmentioning
confidence: 93%
“…Infant post-discharge outcomes were particularly positive among infants from the SFR NICU environment whose mothers also showed high levels of maternal involvement [32]. While a retrospective cohort study of parental skin-to-skin holding of extremely preterm infants, defined by the study's authors as GA < 27 weeks, in the NICU showed a positive but nonsignificant relationship between parents who skin-to-skin held and infant communication development [33], the Family Nurture Intervention trial demonstrated improved cognitive and language outcomes at the 18 month follow-up assessment between intervention and control groups [34]. A longitudinal cohort study followed 81 parent-infant triads over 4–5 years after recording parental visitation, blanket holding, and skin-to-skin holding patterns while preterm infants were hospitalized in the NICU.…”
Section: Resultsmentioning
confidence: 93%
“…One prospective study found that preterm infants (25–34 weeks gestation) who received skin-to-skin care in the NICU obtained higher BSID-II cognitive scores at age 6-months compared to infants who received standard care (57). A more recent retrospective study, however, reported non-significant associations between hours of skin-to-skin care in the NICU and cognitive outcomes of extremely preterm infants (<27 weeks gestation) at ages 6- and 12-months (91). Discrepancy in findings may be attributed to differences in infant clinical characteristics, and the fact that one study (91) analyzed hours of skin-to-skin care using a median split which potentially masked linear associations with cognitive scores (92).…”
Section: Longer-term Child Outcomesmentioning
confidence: 97%
“…Follow-up studies are now linking single family NICU rooms with language outcomes in childhood, however, the findings have been mixed (85,89,90,91). For example, one study found that compared to VPT infants placed in an open-bay wards ( n =40), VPT infants placed in single family rooms ( n =46) obtained lower BSID-III language scores ( d =.61) at age 2-years (85).…”
Section: Longer-term Child Outcomesmentioning
confidence: 99%
“…Healthy infants whose fathers participated in their care had fewer crying episodes after caesarean birth (Erlandsson et al, 2007), improved breastfeeding exclusivity and duration (Hunter & Cattelona, 2014) and more regular sleep patterns (Tikotzky et al, 2011) than those whose fathers were not involved. Father involvement, specifically skin-to-skin contact (Gonya, Ray, Rumpf, & Brock, 2017), has been shown to improve preterm infant cognitive development (Kmita et al, 2014). Father involvement also contributes to a shorter length of hospital stay for preterm infants (Ortenstrand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%